Performance Prediction and Geometry Optimization for Application of Pump as Turbine: A Review - Liu, Ming; Tan, Lei; Cao, Shuliang (Frontiers in Energy Research, 2022)
Pump as Turbine (PAT) is a technically and economically effective technology to utilize small/mini/micro/pico hydropower, especially in rural areas. There are two main subjects that influence the selection and application of PAT. On the one hand, manufacturers of pumps will not provide their characteristics under turbine mode, which requires performance prediction methods. On the other hand, PAT efficiency is always slightly lower than pump, which requires further geometry optimization. This literature review summarized published researches related to performance prediction and geometry optimization, aimed at guiding for selection and optimization of PAT. There exist four categories of performance prediction methods currently, namely, using BEP (Best Efficiency Point), using specific speed, loss modeling, and polynomial fitting. The using BEP and loss modeling methods are based on theoretical analysis, while using specific speed and polynomial fitting methods require statistical fitting. The prediction errors of published methods are within ±10% mostly. For geometry optimization, investigations mainly focus on impeller diameter and blade geometry. The influence of impeller trimming, blade rounding, blade wrap angle, blade profile, blade number, blade trailing edge position, and guide vane number have been studied. Among published methods, the blade rounding and forward-curved impellers are the most effective and feasible techniques.